Interdisciplinary learning combining engravings and poems by teachers in initial training - Peña-Acuña, Beatriz; Assaleh Assaleh, Samir (Frontiers in Education, 2024)
This article quantitatively analyzes the perception of a combined interdisciplinary practice of engraving and poetry by 63 teachers in initial training. The aim is to find a correlation between age and gender with respect to the three dimensions that constitute interdisciplinarity. A moderate positive correlation of age with the dimension perception of skills and a weak correlation with the dimension's perception of knowledge and interdisciplinary attitude are inferred. We conclude the convenience of education in the interdisciplinary perspective, both from pre-university and university levels, as a preparation for students to face the complex.